Pandemic and digitalization: experience of a sociological anamnesis - Korshunov, Gennady P. (Journal of the Belarusian State University. Sociology, 2020)
On the basis of current conditions and global development trends, the article presents a version of the author’s analysis of the social consequences of the COVID-19 pandemic. Particular attention the author pays to the «double problematization» of social practices caused by the development of digital practices and the negative experience of living a pandemic at the micro, meso and macro levels.